Turbo‐coded secure and reliable quantum teleportation. Issue 1 (14th May 2020) - Cane, Rosie; Xie, Wanwan; Ng, Soon Xin
Abstract : Quantum teleportation allows an unknown arbitrary quantum state to be transmitted between two separate locations. To achieve this, the system requires both classical and quantum channels, for communicating two classical bits and an entangled quantum bit from the transmitter to the receiver. It is commonly assumed that both channels are error‐free, however, under realistic conditions, this is unlikely to be the case. This study proposed and investigated a secure and reliable quantum teleportation scheme when both classical and quantum channels exhibit errors. It was found that the security and reliability of the teleportation could be improved when powerful turbo codes are employed.